4(3x-6)-4=4(x-2)+44

Simple and best practice solution for 4(3x-6)-4=4(x-2)+44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-6)-4=4(x-2)+44 equation:


Simplifying
4(3x + -6) + -4 = 4(x + -2) + 44

Reorder the terms:
4(-6 + 3x) + -4 = 4(x + -2) + 44
(-6 * 4 + 3x * 4) + -4 = 4(x + -2) + 44
(-24 + 12x) + -4 = 4(x + -2) + 44

Reorder the terms:
-24 + -4 + 12x = 4(x + -2) + 44

Combine like terms: -24 + -4 = -28
-28 + 12x = 4(x + -2) + 44

Reorder the terms:
-28 + 12x = 4(-2 + x) + 44
-28 + 12x = (-2 * 4 + x * 4) + 44
-28 + 12x = (-8 + 4x) + 44

Reorder the terms:
-28 + 12x = -8 + 44 + 4x

Combine like terms: -8 + 44 = 36
-28 + 12x = 36 + 4x

Solving
-28 + 12x = 36 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-28 + 12x + -4x = 36 + 4x + -4x

Combine like terms: 12x + -4x = 8x
-28 + 8x = 36 + 4x + -4x

Combine like terms: 4x + -4x = 0
-28 + 8x = 36 + 0
-28 + 8x = 36

Add '28' to each side of the equation.
-28 + 28 + 8x = 36 + 28

Combine like terms: -28 + 28 = 0
0 + 8x = 36 + 28
8x = 36 + 28

Combine like terms: 36 + 28 = 64
8x = 64

Divide each side by '8'.
x = 8

Simplifying
x = 8

See similar equations:

| 3x/5-12=-15 | | S/7=6 | | 3x-4=.4(y-5) | | r-0.6r=1500 | | 2y+7=9-14 | | 5+75=80 | | -106+8x=146-x | | 6m+9=3m+53 | | x+4x+90=180 | | 9x+9+5x+45=180 | | 216-7x=29x+20 | | 11-5xa=24 | | 2y-4=12y+16 | | 2x-40=170 | | -0.7y-0.6=-0.2+3.4 | | c=xs+z | | 7x-(4x+7)=17 | | 4x+18-3x=-8-11 | | y=.33(36-18) | | 54=3x+6+x | | (-2x+2)-1=-x-(x+3) | | 2(6a+15)=12a+30 | | 2(x^750)=19000000 | | 3/7-1/2 | | y+9=2x+10 | | 2(5x+5)-6=10x+4 | | y=.33(27-18) | | 2x^2-12=4 | | Solvey=4x^4+32 | | 7/3-1/2 | | -2x+3=.75x-.25 | | -2g+4=1+g |

Equations solver categories